126k views
10 votes
Find the y-intercept. 4) 4x + 3y=-3 A) -3 B) 3 C) -5/2 D) -2/5

User Slaus
by
4.8k points

1 Answer

12 votes

Answer:

Please check the explanation.

Explanation:

Given the equation


4x + 3y=-3

We know that the value of the y-intercept can be determined by setting x = 0 and determining the corresponding value of y.

Thus,

substituting x = 0 in the equation


4x + 3y=-3


4(0) + 3y = -3


0+3y = -3


3y = -3

divide both sides by 3


(3y)/(3)=(-3)/(3)

Simplify


y = -1

Therefore, the y-intercept is: -1

Note: it seems that you did not add the right option to chose.

Find the y-intercept. 4) 4x + 3y=-3 A) -3 B) 3 C) -5/2 D) -2/5-example-1
User Nandun
by
5.1k points